2018
DOI: 10.1039/c8tc03829e
|View full text |Cite
|
Sign up to set email alerts
|

On the use of surfactants for improving nanofiller dispersion and piezoresistive response in stretchable polymer composites

Abstract: Conducting polymer composites are increasingly investigated for the development of piezoresistive materials for sensor applications due to their outstanding electromechanical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 43 publications
1
30
0
Order By: Relevance
“…Polymer-based composites with appropriate electrical conductivity can show electrical resistance variation proportional to the mechanical stimulus applied to the composite, increasing the resistance while the samples are stressed and decreasing when sample recovers to the initial deformation (Figure 9A). Nevertheless, there was an initial reduction of the electrical resistance with the number of loading cycles, suggesting a rearrangement of the conductive network with deformation—a typical electromechanical behavior of elastomeric polymer composites [16,31,37]. It has been shown that after some aging cycles the mechanical and electrical signals tend to stabilize, leading to materials with a stable electromechanical response that is suitable for applications [18].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymer-based composites with appropriate electrical conductivity can show electrical resistance variation proportional to the mechanical stimulus applied to the composite, increasing the resistance while the samples are stressed and decreasing when sample recovers to the initial deformation (Figure 9A). Nevertheless, there was an initial reduction of the electrical resistance with the number of loading cycles, suggesting a rearrangement of the conductive network with deformation—a typical electromechanical behavior of elastomeric polymer composites [16,31,37]. It has been shown that after some aging cycles the mechanical and electrical signals tend to stabilize, leading to materials with a stable electromechanical response that is suitable for applications [18].…”
Section: Resultsmentioning
confidence: 99%
“…Due to geometry and nanofiller agglomerations, composites with nanocarbonaceous fillers need well-controlled manufacturing processes in order to obtain composites with homogeneous and uniform overall properties [12]. Homogeneous nanofiller distribution and dispersion within the polymer matrices also depend on the fillers (van der Waals interactions and geometry) [6,13,14], polymer type [13,15], or surfactant [13,16] incorporation into the composite, as well as on the processing method, as already discussed [13,15].…”
Section: Introductionmentioning
confidence: 99%
“…SNs/polyester nanocomposites have gained great concern due to their excellent performance and large application potential. The dispersion of SNs in polyester matrix is the key parameter determining final performances of the composite materials [147,148]. To date, three methods can achieve good dispersion of fillers in polyester [149,150], including physical blending, sol-gel processes, and in situ polymerization, which will be introduced in detail as follows.…”
Section: Processing Methods Of Sns/polyester Nanocompositesmentioning
confidence: 99%
“…[18] Disadvantages of CNT are the various chiralities, diameters, lengths and impurities, as well as aggregation during their processability. [18,19] Therefore, the outstanding properties of the CNT cannot yet be fully translated to the corresponding polymer composites. [18] Chemical modifications in CNT can decrease their aggregations and improve CNT-polymer affinity.…”
Section: Introductionmentioning
confidence: 99%